Interaction of Cu(II) with Cytosine in Britton-Robinson Buffer Solution - A Cyclic Voltammetric Study (Dhaka University Journal of Science, 2015)
Electrochemical redox behavior of Cu(II) at different pH in Britton-Robinson (BR) buffer solution has been investigated using cyclic voltammetry at glassy carbon electrode (GCE). Cu(II) shows a cathodic peak and a hump-like peak, and an intense anodic peak at pH, 0.59, 1.59, 3.01 and 4.08. Although at lower pH (0.59 and 1.59) a cathodic peak, a hump and an anodic peak are observed, at higher pH (3.01 and 4.08) the hump-like cathodic peak disappeared. Cyclic voltammetry has also been used to observe the interaction of Cu(II) with cytosine in BR buffer solution at various pH. A reasonably strong interaction between Cu(II) and cytosine at different Cu(II)/cytosine molar ratio is observed at all the studied pH. However, maximum interaction occurs at 1:4 molar ratio at pH 4.08, this is perhaps the most suitable condition for Cu(II)-cytosine interaction. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21765 Dhaka Univ. J. Sci. 63(1): 31-36, 2015 (January)